Concentration of CO2 in the Local Working Area during the Joint Operation of a Gas Infrared Heater and an Air-Exchange System; Energies; Vol. 17, iss. 1 - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Salikhov F. Yu. Feliks Yurjevich (2023, 2023)
Title screen